The triglyceride/HDL cholesterol ratio and TyG index to predict coronary artery calcium, epicardial fat and outcome in the general population. (14th October 2021) - Chiappino, S; Aimo, A; Neglia, D; Martini, N; Della Latta, D; Susini, C; Piagneri, V; Storti, S; Passino, C; Emdin, M
Abstract: Background: The ratio between triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C) and the triglyceride-glucose (TyG) index predict the severity of coronary atherosclerosis and outcome in patients with chronic coronary syndrome. We investigated the relationship between TG/HDL-C and TyG and coronary artery calcium (CAC), the volume of the pro-atherogenic epicardial fat, and survival in a primary prevention setting. Methods: Between May 2010 and October 2011, subjects aged between 45 and 75 years living in Montignoso (Tuscany, Italy) and free from known cardiovascular disease were invited to participate to a screening including a computed tomography (CT) scan. Results: Study participants (n=1, 382) were aged 61 years (interquartile interval 54–68), 45% were men, and their 10-year risk of death or myocardial infarction based on the Framingham risk score was 5% (2–10%). CAC and epicardial fat volume (EFV) increased significantly across quartiles of TG/HDL-C and TyG. The TG/HDL-C and TyG displayed weak correlations with CAC and stronger correlations with EFV. The TG/HDL-C and TyG did not predict CAC independently from other baseline variables, while they both independently predicted EFV. Over 10 years (9.5–10.5), 103 individuals died (8%), and 36 patients experienced the composite endpoint of cardiovascular death or urgent revascularization during 10.1 years (9.6–10.6). The risk of all-cause death and the composite cardiovascular endpoint increased with TG/HDL-C and TyG. TG/HDL-C and TyG were univariable predictors of all-cause death and the composite cardiovascular endpoint. Nonetheless, TG/HDL-C and TyG lost their prognostic value for the composite cardiovascular endpoint when adjusting for CAC. Conclusions: In subjects from the general population, the TG/HDL-C and TyG predict CAC and EFV. TG/HDL-C and TyG are also predictive of cardiovascular death or urgent coronary revascularization, although not independently from CAC. FUNDunding Acknowledgement: Type of funding sources: None.